Eco-friendly synthesis of gold nanoparticles by marine microalgae Synechococcus moorigangae: Characterization, antimicrobial, and antioxidant properties - A'liyatur Rosyidah; Debora C. Purbani; Riyona D. Pratiwi; Sjaikhurrizal E. Muttaqien; Nawarat Nantapong; Mega F. Warsito; Muhammad N. Fikri; Feliadewi Ruth; Nunik Gustini; Gita Syahputra; Mohamad Padri; Diah R. Noerdjito; et al. (Kuwait Journal of Science)
Gold nanoparticles (AuNPs) synthesized through green synthesis have the potential for application in various biomedical sectors. This study demonstrates the optimization, synthesis, and characterization of AuNPs using marine microalga, Synechococcus moorigangae strain InaCC M208, isolated from Jakarta Bay, Indonesia. Optimization of the synthesis process focused on three parameters: temperature, ratio of precursor-to-extract, and incubation time. The AuNPs were characterized using various techniques, including UV–Vis spectroscopy, TEM, XRD, FT-IR, PSA, and EDX spectroscopy. The ethanol extract of S. moorigangae InaCC M208 was responsible for the reducing and stabilizing agent during the AuNPs synthesis. The optimized conditions for synthesis were found to be a precursor-to-extract ratio of 1:1 at 37 °C for 22 h. The UV–Vis spectra of the synthesized AuNPs (Syn-AuNPs) exhibited a surface plasmon resonance at 552 nm. According to FT-IR, various phytoconstituents from the extract contributed to the reduction and stabilization of Syn-AuNPs. Syn-AuNPs exhibited a spherical form with an average size of 8.2 nm and a zeta potential of −21.5 mV. Notably, these Syn-AuNPs exhibited antibacterial efficacy against the pathogenic Staphylococcus aureus InaCCB4, Escherichia coli InaCC B5, Klebsiella pneumoniae 1617, Pseudomonas aeruginosa N90PS, and E. coli 8654. Additionally, Syn-AuNPs also demonstrated antioxidant capacities against DPPH radicals. It is possible to readily scale up this environmentally friendly synthesis technique for future studies, and AuNPs produced through microalgae-mediated green synthesis have substantial promise for nanomedicine applications.